Fads, Martingales, and Market Efficiency - Lehmann, Bruce N. (Quarterly Journal of Economics, 1990)
Predictable variation in equity returns might reflect either (1) predictable changes in expected returns or (2) market inefficiency and stock price "overreaction." These explanations can be distinguished by examining returns over short time intervals since systematic changes in fundamental valuation over intervals like a week should not occur in efficient markets. The evidence suggests that the "winners" and "losers" one week experience sizeable return reversals the next week in a way that reflects apparent arbitrage profits which persist after corrections for bid-ask spreads and plausible transactions costs. This probably reflects inefficiency in the market for liquidity around large price changes.